Peran Job Embeddedness dan Perceived Organizational Support terhadap Organizational Citizenship Behavior pada Karyawan - Tentama, Fatwa; Adisti, Adisti (JURNAL PSIKOLOGI, 2024)
This study aims to investigate the impact of job embeddedness and perceived organizational support on organizational citizenship behavior. Participants in this study were 70 permanent employees Nasmoco company in Janti. Participants obtained nonprobability with saturated sampling technique. The scale in this study uses a Likert scaling model, namely on the scale of organizational citizenship behavior, the scale of job embeddedness, and the scale of perceived organizational support. The data analysis was carried out using multiple linear regression analysis with of SPSS V.21. The findings in this study are in line with the three proposed hypotheses. First, simultaneously job embeddedness and perceived organizational support contribute to organizational citizenship behavior. Second, partially job embeddedness is related to organizational citizenship behavior. Third, partially perceived organizational support can be a predictor of organizational citizenship behavior. The effective contributions generated by job embeddedness and perceived organizational support contribute to organizational citizenship behavior by 68.8%, thus job embeddedness and perceived organizational support can predict organizational citizenship behavior.